Human potential and capital of BRICS countries in sustainable development goals system - Ugnich Ekaterina; Kazakova Aminat; Tkacheva Olga (BIO Web of Conferences)
It is of great importance to recognize the potential of humanity at the national level and to strive to realize it in order to achieve sustainable development goals. The paper attempts to shed light on the features of human potential and human capital in BRICS countries through the lens of sustainable development goals. Furthermore, it illustrates the interconnection between human capital and economic growth. The Human Potential Index (HDI) and Human Capital Index (HCI) are presented as key indicators of human capital development and human potential in BRICS countries. We would like to respectfully propose a potential link between these indices and sustainable development goals. The research is based on an analysis of the relationship between the HDI and HCI, as well as the HCI and GDP (PPP) of the BRICS countries in 2024, with a view to identifying potential areas for further investigation. The results of the analysis indicate a high correlation between the level of development of human potential and human capital, with a Pearson correlation coefficient of 0.84 for the HDI and HCI of BRICS countries. The analysis, which is based on the con-struction of a positioning map, has allowed us to propose a tentative division of the BRICS countries into three groups. It would be fair to say that three countries (UAE, Saudi Arabia and Russia) are in a relatively privileged position in terms of their NSI and GDP (PPP) per capita. The group of countries with relatively low GDP (PPP) per capita and high HCI includes two countries: China and Iran. The group with low levels of both HCI and GDP (PPP) per capita includes the remaining five BRICS countries. The presented cross-country analysis could potentially serve as a tool for identifying potential avenues for human capital development, economic growth, and inter-country cooperation of the BRICS countries in the context of achieving sustainable development goals.